The Contribution of Discipleship-Conceptualised PAK to the Spiritual Maturity of Ministers in the Baithani Kadosh Christian Church - Ivone Sri Wengkau; Tonny Andrian Stefanus; Maria Titik Windarti (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article examines the contribution of the Christian Religious Education Programme with the concept of discipleship to the spiritual maturity of ministers at Baithani Kadosh Christian Church. Using a qualitative approach through a literature review, this research explores the literature on theology, Christian education, and the practice of discipleship in the context of church ministry. Analyses were conducted by integrating discipleship theories, spiritual leadership strategies, and spiritual formation practices that have been implemented in PAK. The results of the study show that the PAK concept of discipleship not only enhances the leadership competence of God's servants, but also deepens their spiritual maturity through personal transformation, increased understanding of the Bible, and the application of Christian values in daily life. This finding confirms the importance of the discipleship programme as one of the strategic instruments in shaping a mature and relevant spiritual character in church ministry.